EVALUATION OF VALUE STOCKS VS GROWTH STOCKS AND SMALL SIZE STOCKS VS BIG SIZE STOCKS - , Niza Arumta ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Past studies have shown that alternative candidates for the best variables that explain stock prices (returns) are two popular metrics, size and price-to-earnings ratio of investment strategy. Growth Stocks associated with high PER and vice versa. Likewise, Small Size Stocks related to low market capitalization and Big Size Stocks related to high market capitalization. Recently, It has been debatable case that people have argued about value outperformed the growth investment strategies and small outperform big size stocks. Hence, the research attempts to address some of the issues about the validity of value stocks and growth stocks investment strategies and small and big size stocks. The research applies the data of non financial companies at 2009. To evaluate the performance of those two metrics, the monthly stock price of sorted data rank based on PER and size and then the data is run under sequence steps to measure the Sharpe Index of Value Stocks, Growth Stocks, Small Stocks, and Big Stocks. Evaluation is ensued between Value Stocks and Growth Stock, next is between Small Stocks and Big Stocks. The higher the value of Sharpe Index the greater the performance. Furthermore, the results of Sharpe measurement is benchmarked over the market value. The research findings show that there is no difference between Value Stocks and Growth Stocks, however there is an indication that Value Stocks works slightly better than Growth Stocks. Similarly, there is no difference between Small Stocks and big Stocks, however Small Stocks works better than big Stocks on Sharpe measurement basis.